An optical synchronous up counter based on electro-optic effect of lithium niobate based Mach–Zehnder interferometers - Kumar, Santosh; Singh, Gurdeep; Bisht, Ashish; Amphawan, Angela (Springer US, 2015)
Sequential circuits have the ability to store, retain and then retrieve information when needed at a later time.They act as storage elements and have memory. However, due to ever increasing demand of data rate, already existing electronic signal processing devices have become obsolete due to their large latency.To overcome the existing bottleneck, a 4-bit synchronous up counter using electro-optic effect of Mach–Zehnder interferometer has been proposed. The study is carried out by simulating the proposed device with beam propagation method.